Pengaruh Perubahan Suhu terhadap Nilai Panjang Gelombang Fiber Optik yang Difungsikan Sebagai Sensor Suhu - Alna Destra Shafira; Yoyok Heru Prasetyo Isnomo; Azam Muzakhim Imamuddin (Jurnal Jaringan Telekomunikasi, 2021)
In this study we can determine the effect of temperature on wavelength and frequency on fiber optic media by using a splitter by looking at the measured wavelengths when the optical fiber is heated using an aluminum intermediate as a heat sensor. With temperatures to be used ranging from 270?C to 400?C. The measurement was carried out using an Optical Spectrum Analyzer (OSA) device. From the temperature variations given, the conclusion is that the greater the temperature given, the farther the wavelength shift and the smaller the resulting frequency. The wavelength produced on the fiber optic splitter cable 1 to the fiber optic splitter cable 4 has almost the same wavelength value starting from a temperature of 270 ° C- 400 ° C. the difference occurs when the cable before the splitter and after the seplitter. The validity level in each splitter has a different persesn value such as the splitter has a validity value of 99.80%, splitter 2 has a validity of 99.72%, Splitter 3 has a validity of 99.72% and splitter 4 has a validity of 99.70%